2020
DOI: 10.1016/j.ijpara.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term production effects of clinical cryptosporidiosis in neonatal calves

Abstract: Cryptosporidiosis can have a devastating effect in neonatal calves, resulting in diarrhoea, dehydration and, in severe cases, death of the animal. The disease is caused by Cryptosporidium spp. and is one of the most common causes of calf enteritis in the UK. The parasite is very difficult to remove from the farm, as the oocysts have a tough outer wall which enables the parasite to survive for several months in moist temperate environmental conditions and it is difficult to kill oocysts with common disinfectant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…With an infectious dose for neonatal calves as low as 17 oocysts (32), ensuring that young stock are not exposed to an infectious dose on farms where other stock are already infected can be challenging. As with humans (see previous subsection), it has also been shown that severe cryptosporidiosis in calves and lambs may have long-term consequences regarding growth, weight gain, and productivity (33)(34)(35), as well as the more immediate effects from the acute infection.…”
Section: Veterinary Health Impactsmentioning
confidence: 83%
“…With an infectious dose for neonatal calves as low as 17 oocysts (32), ensuring that young stock are not exposed to an infectious dose on farms where other stock are already infected can be challenging. As with humans (see previous subsection), it has also been shown that severe cryptosporidiosis in calves and lambs may have long-term consequences regarding growth, weight gain, and productivity (33)(34)(35), as well as the more immediate effects from the acute infection.…”
Section: Veterinary Health Impactsmentioning
confidence: 83%
“…This study highlighted the reduced growth associated with a C. parvum and BCoV infection, and the increased risk of respiratory disease associated with a C. parvum infection. A recent paper identified the effect of C. parvum on long-term weight reduction (Shaw et al, 2020), but no studies have specifically identified BCoV as having an effect on the growth of dairy calves. This reduction in growth was likely due to damage to enterocytes, leading to villous atrophy and ultimately malabsorption of nutrients (Cho and Yoon, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They are responsible for significant mortality in both young children [1,3] and neonatal farm animals [4][5][6][7][8]. In addition, cryptosporidiosis has been associated with retarded growth in humans and farm animals [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%